A comunicação pública cidadã: análise textual fundamentada sobre o grupo "frente de luta Goiás contra o aumento da passagem de ônibus" em Goiânia - Leite, Quézia de Alcântara Guimarães (2015)
Today the new communication environment, the internet, heavily affects social mobilization. At this environment, considered the New Virtual Public Sphere, individuals interact and generate collective actions never seen before. Some authors refer to this process as Horizontal Communication, while others simply name it as an exercise of citizenship. Because of the intersection of the three terms: Horizontal Communication, Public Sphere and Social Mobilization, there is the new concept of Public Citizen Communication. This concept is the process of dialogue between social actors functioning in the public area of contemporary society. In order to verify if the process really occurs, a textual analysis based on Grounded Theory was applied on the communicative actions of the group “Frente de Luta Goiás Contra o Aumento da Passagem de Ônibus”. The group was part of the demonstrations and street protests on the “Outono Brasileiro” in 2013 against the readjustment of public transportation fare in the main cities of the country. Social Networks had substantial part on these demonstrations. This lead to significant analysis by many intellectuals, academics and society in general, regarding the potential of communication involved in social networks. The verification was that in the communicative actions of the activist group “Frente de Luta Goiás”, social networks were in fact used instrumentally. What happened was a scathing mobilization that proved the existence of opinion leadership and social mediation that could be responsible for the collective action of nearly 70,000 people in Goiânia, similarly to the national level demonstrations with more than 1,400,000 people at 200 Brazilian cities on 20th of July of 2013.